The perception of men's intimacy in the fin de siècle : a consideration via Delville's The School of Plato. - De Keukeleire, Thijs ([Oxford] : Association for Art History, 2020)
Fonds Suzan Daniel (FSD)
Artikel oorspronkelijk verschenen in Art History (2020)
Engels
Brochure